The research of Henry Lansdell «Russian Central Asia» of 1885 as one of the primary source materials - Zhangabulova, Zh.M.; Orazaeva, Zh.Zh. (KU Publ., 2021)
The article analyses the scientific researches, which are related to the study of the role of Central Asia in the formation of the Tsarist Empire. The XIX century entered world history as a period and stage when the views of European political figures, scientific researchers, entrepreneurs and the military were riveted to previously unknown and inaccessible corners of Asia. Furthermore, the general worldviews of foreign and Russian scientists of the XIX century were also analyzed. Particular attention was paid to the study of natural conditions, history, ethnography, religion and culture of the peoples of Central Asia. The authors singled out and analyzed the scientific work of 1885 by the well-known researcher Henry Lansdell «Russian Central Asia» as one of the primary sources in a broad historical and socio-cultural context.
Генри Лансделлдің «Орыс Орталық Азиясы» атты 1885 жылғы зерттеуі ең бастапқы дереккөздердің бірі ретінде
Исследование Генри Лансделла «Русская Центральная Азия» 1885 года как один из первоисточников
Keywords: historical sources; travelers; researchers; Henry Lansdell; Central Asia; the «Great Game»; scientific researches; Russian Empire; British Empire; confrontation in the XIX century; «Russian Central Asia»